The Securitization of China's Technology Companies in the United States of America - Giandi Kartasasmita; Andrea Prisca Kurnadi (Parahyangan Center for International Studies, 2020)
This paper aims to explain the securitization process of China’s technology companies by the U.S Government. Whilethe U.S has been aware of the cyber threat since 1998, before Trump's presidency, the U.S. Government had nevertaken drastic measures against foreign technology companies based on national security pretext. This paper revealedthat the U.S. Executive has succeeded in securitizing the Chinese hardware and software companies, proved by theincreasing number of U.S. Citizens, see China as a major threat to the U.S.